A comparison of inequality and living standards in Canada and the United States using an expanded measure of economic well-being - Edward N. Wolff; Ajit Zacharias; Thomas Masterson; Selçuk Eren; Andrew Sharpe (Levy Economics Institute of Bard College, 2012)
We use the Levy Institute Measure of Economic Well-being (LIMEW), the most comprehensive income measure available to date, to compare economic well-being in Canada and the United States in the first decade of the 21st century. This study represents the first international comparison based on LIMEW, which differs from the standard measure of gross money income (MI) in that it includes noncash government transfers, public consumption, income from wealth, and household production, and nets out all personal taxes. We find that, relative to the United States, median equivalent LIMEW was 11 percent lower in Canada in 2000. By 2005, this gap had narrowed to 7 percent, while the difference in median equivalent MI was only 3 percent. Inequality was notably lower in Canada, with a Gini coefficient of 0.285 for equivalent LIMEW in 2005, compared to a US coefficient of 0.376 - a gap that primarily reflects the greater importance of income from wealth in the States. However, the difference in Gini coefficients declined between 2000 and 2005. We also find that the elderly were better off relative to the nonelderly in the United States, but that high school graduates did better relative to college graduates in Canada.
Keywords: D31; D63; P17; 330; well-being; living standards; inequality; income; international comparisons